The Mapping Verses and Application of the Linguistic Approach and Ushul Fiqh Toward the Law of Adultery - Rasidin, Mhd.; Witro, Doli; Diana, Rahmi; Muna, Moh. Nailul; Sidqi, Imaro; Daini, Hening Sukma (Sharia Faculty of State Islamic Institute (IAIN) Palangka Raya, 2024)
It becomes a dilemma when Muslim communities cannot apply Islamic criminal law. In fact, a law is not only to be understood but also believed to be true by Muslims themselves. So, it is appropriate that the punishment for adultery is less likely to have a deterrent effect on the perpetrator. This is because, apart from conventional criminal law being poorly understood by the Muslim community, the sanctions are also quite light so that the deterrent effect desired by law enforcers cannot be realized. This research aims to analyze adultery law by applying linguistic approaches and ushul fiqh to adultery law. This type of research is normative law using a language and ushul fiqh approach. The data sources were primary and secondary, while data collection techniques were observation and literature study. The results of this research show that adultery is analyzed using a language and ushul fiqh approach is the perpetrator of a criminal act who deliberately commits the elements of inserting male genitalia into female genitalia (in intercourse), which is unlawful according to the substance of the act, not because subḥāt and women bring lust. The punishment for adultery is to jilīd one hundred times. This penalty can be applied if the legal action has been legal before the court by presenting four witnesses. The stipulated punishment cannot be changed with other types of punishment because the punishment is regulated by the text of the Al-Quran.